A Human Activity Approach to User Interfaces - Bødker, Susanne (DAIMI Report Series, 1989)
This paper presents a framework for the design of user interfaces which starts out from the work situations where computer based artifacts are used: The framework deals with the role of the user interface in purposeful human work. Human activity theory is used in this analysis. The purpose of the paper is to make the reader curious and hopefully open his or her eyes to a somewhat different way of thinking about the user interface. The paper applies examples of real-life interfaces to support this process, but it is not the purpose of the paper to give a systematic presentation of empirical results. The paper focuses on the role of the computer application in use. Thus, it is necessary to deal not only with the relation between the human being and the computer, but also with other surounding conditions for work. Human experience and competence is dealt with as rooted in the practice of the group which conducts the specific work activity